Quem tem a força? as relações de poder intrapartidárias em perspectiva multinível - Leveguen, Brina Deponte (Universidade Federal de São Carlos, 2018)
Considering the Brazilian institutional and political context, the object of analysis is the multilevel party leadership structure. The objective of the research is to analyze intra-party organizational dynamics and control mechanisms used by leadership, with emphasis on the use of Provisional Committees. The research design involves the nine parties with the highest number of governing bodies: PMDB, PT, PFL / DEM, PSDB, PP, PDT, PSB, PR and PTB from the pre-election period in 2006 to the post-election period in 2016. The hypotheses are 1- the ideological spectrum exerts an influence on the degree of centralization and autonomy of the governing bodies; 2- the electoral performance impacts on the structure of the state organs. The methodology considers comparative analysis through multiple documentary research, including partisan statutes, party and electoral laws, and partisan documents that indicate interventions at the national level of state bodies. The result is that ideology has an impact on formal organization, especially on partisan statutes and the dismissal of Provisional Committees. Electoral coordination was also a variable that influences the occurrence of interventions, especially in the PT and PSDB, which focus on the presidential election.
Who has the power? intraparty relations in a multi-level perspective
Keywords: Partidos políticos; Elites dirigentes; Estruturas decisórias; Organização interna; Comissão provisória; Political parties; Leadership; Decision-making structures; Internal organization; Provisional committee; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO